Functional traits underlying performance variations in the overwintering of the cosmopolitan invasive plant water hyacinth (Eichhornia crassipes) under climate warming and water drawdown. Issue 8 (4th August 2022) - Huang, Xiaolong; Ke, Fan; Li, Qisheng; Zhao, Yu; Guan, Baohua; Li, Kuanyi
Abstract: Reports of the Intergovernmental Panel on Climate Change (IPCC) indicate that temperature rise is still the general trend of the global climate in the 21st century. Invasive species may benefit from the increase in temperature, as climate can be viewed as a resource, and the increase in the available resources favors the invasibility of invasive species. This study aimed to assess the overwintering growth of the cosmopolitan invasive plant water hyacinth ( Eichhornia crassipes ) at its northern boundary. Using E. crassipes as a model plant, a cross‐year mesocosm experiment was conducted to determine 17 plant functional traits, including growth, morphological, root topological, photosynthetic, and stoichiometric traits, under climate warming (ambient, temperature rises of 1.5°C and 3.0°C), and water drawdown or water withdrawal (water depths of 1, 10, and 20 cm) treatments. The overwintering growth of E. crassipes was facilitated by climate warming and proper water drawdown, and climate warming played a leading role. A temperature rises of 3.0°C and a water depth of 10 cm were the most suitable conditions for the overwintering and rooting behavior of the plant. Controlling the temperature to within 1.5°C, an ambitious goal for China, still facilitated the overwintering of E. crassipes . With climate warming, the plant can overwinter successfully, which possibly assists it in producing and spreading new ramets in the vernal flood season. The new rooting behavior induced by ambient low temperature may be viewed as a unique growth adaptation strategy for a niche change, as it helps these plants invade empty niches left by dead free‐floating plants on the water surface following winter freezes. With continued global warming, the distribution of the plant may expand northward, and eradication of the plant during the winter water drawdown period may be a more effective strategy. Abstract : A cross‐year mesocosm experiment was conducted using Eichhornia crassipes as a model plant under climate warming and water drawdown. The results revealed that the overwinter survival and growth of E. crassipes was facilitated by the two factors, and climate warming played a leading role. Controlling the temperature to within 1.5°C still facilitated the overwintering of the plant and eradication of the plant during winter water drawdown period may be more effective.